Influence of Artificial Intelligence and Social Media Use on Academic Performance and Mental Health in the Smart Learning Environments - Nur Cahyani; Muh. Rayfan Alfatir Asfian (Journal of Smart Education and Emerging Technology, 2025)
Background/Context: The era of smart learning has significantly transformed the way students interact with technology, particularly through artificial intelligence (AI) and social media. While these technologies provide opportunities for innovation in education, they also present challenges related to academic performance and mental well-being.Objective/Purpose: This study aims to analyze the influence of AI and social media use on the academic performance and mental health of students at State University of Makassar.Method: A quantitative descriptive approach was applied, using a Likert-scale questionnaire distributed to university students. Data were analyzed to identify patterns and relationships between technology use, academic achievement, and psychological conditions.Results: The findings indicate that AI use has a generally positive impact, particularly in supporting the effectiveness of learning and enhancing academic outcomes. In contrast, the influence of social media is more diverse. While moderate use can provide social and emotional support, excessive engagement is linked to anxiety, stress, and reduced focus, negatively affecting mental well-being.Conclusion: The study highlights the dual role of technology in higher education. AI contributes to more effective and personalized learning, whereas social media requires careful management to prevent adverse effects on students’ mental health. These results provide insights for developing strategies that promote a balanced integration of technology in education, ensuring both academic success and psychological well-being in the smart learning era.